2022
DOI: 10.1038/s41598-022-19082-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased terrigenous input from North America to the northern Mendeleev Ridge (western Arctic Ocean) since the mid-Brunhes Event

Abstract: Mid-Brunhes Event (MBE) occurred at approximately 420 ka between Marine Isotope Stage 11 and 12, and is considered the most pronounced climatic shift during the last ~ 800 kyrs. On the other hand, it is unclear if the MBE was global, despite being observed in the high-latitude Northern Hemispheric cryosphere in terms of climate systems. A 5.35-m long gravity core ARC5-MA01 was obtained from the northern Mendeleev Ridge in the western Arctic Ocean to track the paleoenvironmental changes in terms of the terrigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…2021; Park et al . 2022) from the northern Mendeleev Ridge provide information about sedimentological and organic matter properties, in addition to 230 Th xs profiles allowing for the set up of similar chronostratigraphies. As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2021; Park et al . 2022) from the northern Mendeleev Ridge provide information about sedimentological and organic matter properties, in addition to 230 Th xs profiles allowing for the set up of similar chronostratigraphies. As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…a situation when sedimentation was mainly governed by deep currents and/or meltwater plumes beneath the ESIS, a situation when primary productivity was extremely low. Unfortunately, aside from our study core E25, only two sites (MC11 and MA01; Not & Hillaire-Marcel 2010;Xiao et al 2020;Xu et al 2021;Park et al 2022) from the northern Mendeleev Ridge provide information about sedimentological and organic matter properties, in addition to 230 Th xs profiles allowing for the set up of similar chronostratigraphies. As illustrated in Fig.…”
Section: Resilient Ice Cover Off the East Siberian Shelf During The L...mentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al (2021) reported that the majority of sediments in the Makarov Basin were derived predominantly from Siberian marginal sources rather than North American sources. However, during glacial and deglacial periods marked by the formation and disintegration of ice sheets, a large amount of glacier-derived sediments were transported from North America to the western Arctic Ocean due to the substantial terrigenous supply facilitated by ice-rafting from the Canadian Arctic (Dong et al, 2017;Fagel et al, 2014;Park et al, 2017Park et al, , 2022Schreck et al, 2018;Stein, Matthiessen, Niessen, Krylov, et al, 2010Ye et al, 2022). Terrigenous sediments in the Arctic Ocean are primarily derived from riverine input and coastal erosion, as well as from icebergs during glacial and deglacial periods (Stein, 2008).…”
Section: Backgroundsmentioning
confidence: 99%
“…In the western Arctic Ocean, detrital carbonates, particularly dolomite, have been commonly used as indicators of LIS extension in the Canadian Arctic (e.g., Dong et al, 2017;Not & Hillaire-Marcel, 2012;Park et al, 2017Park et al, , 2022Phillips & Grantz, 2001;Polyak et al, 2009;Stein, Matthiessen, Niessen, Krylov, et al, 2010). Based on the dolomite content in core 41GC, the impact of the LIS on sediment deposition in the western Arctic Ocean began at around 790 ka (MIS 19/20), corresponding to the complete termination of the MPT (Figure 3).…”
Section: Evolution Of the Laurentide Ice Sheet Since The Early Pleist...mentioning
confidence: 99%